Functional properties and Environmental sustainability of fermented yellow pea flour - Fernando,Warnakulasuriya Chrishan Sumeda (2025)
The growing demand for sustainable and functional plant-based protein sources has positioned yellow pea (Pisum sativum) as a promising candidate in the development of next-generation food products. From a sustainability perspective, yellow pea fermentation represents an environmentally favorable protein source compared to animal derived alternatives. The nitrogen fixing capacity of yellow pea further contributes to sustainable agricultural practices by reducing fertilizer requirement. This study investigates the comparative environmental sustainability and functional properties of yellow pea flour subjected to solid-state fermentation (SSF) and submerged fermentation (SmF), using food-grade microbial strains; Rhizopus oryzae and Lactobacillus plantarum 299v. Functional properties assessed, included water absorption index, water solubility index, water absorption capacity, oil absorption capacity, emulsion activity, emulsion solubility, and pasting properties. Additionally, physicochemical properties such as moisture content, color characteristics and protein content were analyzed. The properties were quantified before and after fermentation. Both SSF and SmF had effect on the functional properties of yellow pea flour, with SSF generally showing superior improvements in water solubility index and protein content. In regard of oil absorption the 48 hour fermented flours had the highest capacities for both methods. The SmF exhibited higher values for moisture content, water absorption index, water absorption capacity and pasting properties. The results reveal that while some of the treatment procedures may lead to higher qualities, some of them may contribute to lower properties of yellow pea flour. Environmental impact was assessed using a cradle-to-gate life cycle assessment (LCA) approach, evaluating climate change during the fermentation process. There was a slight difference in environmental impact between solid state fermentation (6.56 kg CO2-Eq/1 kg) and submerged fermentation (6.41 kg CO2-Eq/1 kg). Incubation stage was identified as the hot spot of the fermentation process. SmF demonstrated a lower environmental impact than SSF due to its reduced energy consumption in anaerobic conditions. In addition, SmF offers better process control and scalability advantages. These findings support the use of yellow pea as a sustainable ingredient in functional food formulations and highlight the potential of batch mode SmF as a more environmental friendly processing method. In conclusion, fermentation markedly enhances the functional and physiochemical profile of yellow pea, supporting its use in a wide range of food applications such as plant-based dairy, meat analogs, and baked goods. Fermentation technique emerges as a more sustainable and efficient technique, aligning with the principles of green processing and circular bioeconomy. These findings underscore the potential of fermented yellow pea as a functional, eco-friendly ingredient for the food industry.
Keywords: Solid-state fermentation; Submerged fermentation; Yellow pea; Food engineering nutrition and food chemistry